The Influence Of General Values On The Behavior Of Modern Society - Madhani, Reny; Harahap, Khairunnisa; br bukit, Rizky delhiana; Zulfitri (Pascasarjana Universitas HKBP Nommensen, 2025)
As formed by God, humans are born as individuals, but as their nature changes and evolves, they become social beings. Why? Because humans require the support and aid of others from the moment of their birth till their death. Humans are unique in their nature, character, interests, and desires in daily life. There are differences between these human interests and aspirations. The relationship between two people will be disrupted if their interests and desires are not the same or even conflicting. This will disrupt the community's peace and security if it is allowed to continue for an extended period of time. Community behavior that conforms to the rules, regulations, and cultural standards is therefore necessary in the community.